2004
DOI: 10.1038/sj.bjc.6602095
|View full text |Cite
|
Sign up to set email alerts
|

Methylation pattern of CDH13 gene in digestive tract cancers

Abstract: Recently, the loss of CDH13 (T-cadherin, H-cadherin) gene expression accompanied by CDH13 promoter methylation was identified in colon cancers. We examined CDH13 methylation in oesophageal and gastric carcinomas. Five of 37 oesophageal cancers (14%) and 23 of 66 gastric cancers (35%) demonstrated abnormal methylation of the CDH13 promoter. Abnormal methylation was frequently found in gastric cancers of patients at all clinical stages just as in E-cadherin, another of the cadherin family, suggesting that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 12 publications
4
20
0
1
Order By: Relevance
“…In the present study, we observed that CDH13 and PGP9.5 are also methylated in gastric mucosae with H. pylori infection, which is consistent with an earlier study showing CDH13 to be aberrantly methylated in gastric cancer (32). CDH13 (also known as H-cadherin) encodes a protein related to the cadherin superfamily of cell adhesion molecules and is involved in suppressing cell growth, invasion, and metastasis (33,34).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we observed that CDH13 and PGP9.5 are also methylated in gastric mucosae with H. pylori infection, which is consistent with an earlier study showing CDH13 to be aberrantly methylated in gastric cancer (32). CDH13 (also known as H-cadherin) encodes a protein related to the cadherin superfamily of cell adhesion molecules and is involved in suppressing cell growth, invasion, and metastasis (33,34).…”
Section: Discussionsupporting
confidence: 92%
“…Highly invasive growth pattern (Berx et al 1998) Up-regulated expression Epithelial ovarian cancer (Sato et al 1998;Maruyama et al 2001;Toyooka et al 2001;Toyooka et al 2002;Roman-Gomez et al 2003;Hibi et al 2004;Sakai et al 2004;Kim et al 2005;Wang et al 2007;Brock et al 2008;Jin et al 2008;Yan et al 2008) LOH and promoter methylation Ovary Skin (BCC and SCC) Diffuse large B cell lymphoma HCC Tumor invasion; increased cell proliferation and resistance to apoptosis (Kawakami et al 1999;Takeuchi et al 2002a;Takeuchi et al 2002b;Ogama et al 2004;Chan et al 2008) Expression in intratumoral endothelium…”
Section: Somatic Mutations Breast (Ilc) Gastric (Dgc) Pancreasmentioning
confidence: 99%
“…[16][17][18] Furthermore, there is a growing body of evidence showing that abnormal methylation of DNA can be an early event in carcinogenesis and can serve as an early cancer detection biomarker, 15 including in EAC. [17][18][19][20] Hypermethylation of CDH13 has been described in many human cancers, 8,14,[21][22][23][24][25][26][27][28][29] including ESCC 24,29 ; however, hypermethylation of CDH13 in precancerous lesions such as Barrett's metaplasia (BE), as well as in BE-associated EAC, is an area that still remains to be explored. We investigated hypermethylation of the CDH13 promoter by real-time quantitative methylation-specific PCR (qMSP) in 259 endoscopic esophageal biopsy specimens of differing histologies and correlated these data with clinicopathological features.…”
Section: Cdh13mentioning
confidence: 99%